Incidence, Degree, and Clinical Effect of Subchondral Bone Overgrowth After Microfracture in the Knee. (August 2016) - Mithoefer, Kai; Venugopal, Vivek; Manaqibwala, Moiz
Background: Subchondral bone overgrowth has been described with variable frequency after microfracture, but little systematic information is available about the clinical incidence, risk factors, or clinical relevance of this phenomenon. Hypothesis: Subchondral overgrowth (1) occurs with high incidence and various degrees after microfracture, (2) is associated with risk factors, and (3) affects clinical outcome score and failure rate. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 84 patients undergoing microfracture in the knee were prospectively followed up to 6 years postoperatively through use of cartilage-sensitive magnetic resonance imaging to detect the incidence of subchondral bone overgrowth. The quantity of the overgrowth was graded systematically and was then correlated to patient and lesion characteristics, surgical technique, validated functional outcome scores, and failure rate. Results: Subchondral bone overgrowth was observed in 62% of patients at a mean of 22 months after surgery. Most bone overgrowth (64%) was low grade and developed during the first 12 months after microfracture. Risk factors for bone overgrowth included high body mass index, defects on the lateral femoral condyle, and aggressive debridement of the calcified cartilage layer. Knee injury and Osteoarthritis Outcome Score results were not significantly different between patients with or without subchondral bone overgrowth. However, 93% of patients who failed microfracture demonstrated osseous overgrowth, and patients with osseous overgrowth showed a significantly higher failure rate (25%) than patients without overgrowth (3.1%; P < .01). Conclusion: Subchondral bone overgrowth is frequently observed after microfracture surgery but is mostly of low grade. Several risk factors were identified that can affect the incidence of this phenomenon. Importantly, subchondral overgrowth is associated with an increased rate of postoperative failure after microfracture.